1993
DOI: 10.1080/02640419308730019
|View full text |Cite
|
Sign up to set email alerts
|

Plasmaß‐endorphin immunoreactivity: Response to resistance exercise

Abstract: Previous research investigating the response of plasma beta-endorphins (beta-EP) to resistance exercise has resulted in equivocal findings. To further examine the effects of resistance exercise on beta-endorphin immunoreactivity, six resistance-trained athletes participated in a three-set series of eight repetitions of isotonic exercise. All exercises were performed at 80% maximal effort. Blood was sampled from the group by venepuncture, both prior to and following the exercise bout, and beta-endorphin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Many studies have demonstrated an increase in the plasma levels of endogenous opioids, mostly β-endorphin, during and after aerobic exercise (5); however, only a few studies have investigated alterations in this parameter when resistance exercise was involved, with equivocal results. Analysis of blood samples of athletes submitted to 3 sets of 8 repetitions at 80% of 1 RM showed no significant change in the circulating β-endorphin levels (14), while a significant increase in plasma β-endorphin levels was detected in men after a high total work-exercise protocol (15).…”
Section: Discussionmentioning
confidence: 82%
“…Many studies have demonstrated an increase in the plasma levels of endogenous opioids, mostly β-endorphin, during and after aerobic exercise (5); however, only a few studies have investigated alterations in this parameter when resistance exercise was involved, with equivocal results. Analysis of blood samples of athletes submitted to 3 sets of 8 repetitions at 80% of 1 RM showed no significant change in the circulating β-endorphin levels (14), while a significant increase in plasma β-endorphin levels was detected in men after a high total work-exercise protocol (15).…”
Section: Discussionmentioning
confidence: 82%
“…More detailed investigations revealed that an anaerobic state, which was reached at a threshold of about 90 % of maximum oxygen consumption and was documented by a blood lactate level of more than 4 mmol/l arterialized blood, leads to a considerable increase of β-endorphin levels in human plasma under exercise [24,26]. Compatible with these findings was the fact that non-exhaustive performance such as heavy resistance exercise, although requiring high muscular activity for short time periods, did not lead to an increase of β-endorphin levels at all [20], even decreased them [21], or only allowed an increase under approximately exhaustive conditions [14]. On the other hand, one would have expected an enhancement of exhaustive exercise-induced β-endorphin release under additional hypoxia which, however, was not observed [5,13].…”
Section: Discussionmentioning
confidence: 97%
“…It should be noted that in group 1, the slight reduction of β-end level was significant (p < 0.05), thus suggesting that the increased β-end in group 2 and 3 most likely resulted from exercise only and not from VC. From previous reports, the intensity and type of exercise for increasing β-end is still unclear, but resistance and moderate intensity exercise did not influence β-endorphin level [46]. …”
Section: Discussionmentioning
confidence: 99%